The Sustainability of Corporate Social Responsibility (CSR) policy among the firms within Indomobil Group have difference performance from stakeholders view. PT Suzuki Indomobil Motor (PT SIM) have some sector that should be priority to be done like opportunity to work in PT SIM for local community and social disintegration between local community and PT SIM worker. For PT Nissan Motors Indonesia (PT NMI) and PT Hino Motor Manufacturing Indonesia (PT HMMI) the sector that should be priority ar - Partogi S. Samosir; Aida Vitayala S. Hubeis; Musa Hubeis; Gunadi Sindhuwinata (Forum Pasca Sarjana, 2011)
The Sustainability of Corporate Social Responsibility (CSR) policy among the firms within Indomobil Group have difference performance from stakeholders view.  PT Suzuki Indomobil Motor (PT SIM) have some sector that should be priority to be done like opportunity to work in PT SIM for local community and social disintegration between local community and PT SIM worker.  For PT Nissan Motors Indonesia (PT NMI) and PT Hino Motor Manufacturing Indonesia (PT HMMI) the sector that should be priority are impact of company existence to increasing of prices of goods and services for local community consumption, planting tree activity, increasing amount of small economic and financial institution.  The policy of CSR should be improvement CSR performance with keep increasing of business growth simultaneous.  The management of CSR activity of Indomobil Group have important role to support company performance as good corporate citizenship in area where company operated especially in factory location.  Positioning of company in stakeholders view is basic step to choose the kind of CSR policy.  To get sustainable CSR especially in automotive industry company should do mapping stakeholders needs and expectation that result priority of atributes.   Key words: CSR, sustainability,stakeholders, company